The Influence Of Total Performance Scorecard To Improving Performance Of Public Sector Organization With Organizational Culture, Innovation Of Management, And Internal Control As Moderating Variables (Case Study In The Hospital Type C In Banyumas) - nugroho, yanuar (Prosiding Seminas, 2011)
ABSTRAK Penelitian ini dilakukan pada kabupaten Banyumas dengan objek rumah sakit swasta dan pemerintah yang bertujuan untuk menganalisis dan membuktikan pengaruh budaya organisasi, inovasi manajemen, dan pengendalian internal terhadap efektivitas implementasi total performance scorecard dalam meningkatkan kinerja rumah sakit, serta menguji implementasikan total performance scorecard untuk mengukur tingkat perbedaan kinerja rumah sakit swasta dan pemerintah. Metode penelitian ini menggunakan metode survei. Teknik pengumpulan data melalui wawancara mendalam, observasi dan kuesioner. Dalam penelitian ini digunakan dua teknik analisis, yaitu analisis kuantitatif dengan menggunakan metode analisis kuantitatif (analisis utama), dan analisis kualitatif deskriptif (analisis tambahan). Hasil penelitian menunjukkan bahwa; 1) Implementasi total performance scorecard berpengaruh terhadap peningkatan kinerja rumah sakit, 2) Budaya organisasi, inovasi manajemen, dan pengendalian internal berpengaruh terhadap efektivitas implementasi total performance scorecard dalam meningkatkan kinerja rumah sakit, 3) Terdapat perbedaan yang signifikan antara implementasi total performance scorecard dalam mengukur kinerja pada rumah sakit pemerintah dan rumah sakit swasta Kata Kunci: total performance scorecard, budaya organisasi, inovasi manajemen, pengendalian internal, dan kinerja rumah sakit ABSTRACT This research was carried out in Banyumas with private and government hospitals as the objects. It aimed to analyze and to demonstrate the influence of organizational culture, innovation of management, and internal control to the effectiveness of the implementation of total performance scorecard in improving hospital performance, and also to examine the implementation of total performance scorecard in measuring the differences performance of private and government hospitals. The method of this research was survey method. Techniques of data collection were depth interviews, observation and questionnaires. In this study, the writer used two techniques of analysis; quantitative analysis by the method of quantitative analysis or statistical test (main analysis), and qualitative descriptive analysis (additional analysis). The results showed that: 1) the implementation of total performance scorecard effects on improving hospital performance, 2) Organizational culture, innovation management, and internal control affect to the effectiveness of the implementation of total performance scorecard in improving hospital performance, 3) There are significant differences between the implementation of total performance scorecard in measuring performance in private and government hospitals. Keywords: total performance scorecard, organizational culture, innovation management, internal control and hospital performance